The potential use of single-particle electron microscopy as a tool for structure-based inhibitor design - Rawson, S. (Acta Crystallogr D Struct Biol, 2017)
Recent developments in electron microscopy (EM) have led to a step change in our ability to solve the structures of previously intractable systems, especially membrane proteins and large protein complexes. This has provided new opportunities in the field of structure-based drug design, with a number of high-profile publications resolving the binding sites of small molecules and peptide inhibitors. There are a number of advantages of EM over the more traditional X-ray crystallographic approach, such as resolving different conformational states and permitting the dynamics of a system to be better resolved when not constrained by a crystal lattice. There are still significant challenges to be overcome using an EM approach, not least the speed of structure determination, difficulties with low-occupancy ligands and the modest resolution that is available. However, with the anticipated developments in the field of EM, the potential of EM to become a key tool for structure-based drug design, often complementing X-ray and NMR studies, seems promising.